Pueblo, Política y nación, siglos XIX y XX - Knight, Alan (1996)
As stated in its title, this article discusses interrelations among peoples, politics, and nationhood during the 19th and 20th centuries, and seeks to apply reasonings derived from Mexican history to the Central America countries.